Acinetobacter baumannii Survival under Infection-Associated Stresses Depends on the Expression of Resistance–Nodulation–Division and Major Facilitator Superfamily Efflux Pumps - Inga V. Leus; Marcela Olvera; Justyna W. Adamiak; Lauren L. Nguyen; Helen I. Zgurskaya (Antibiotics, 2023)
Multidrug efflux transporters are major contributors to the antibiotic resistance of Acinetobacter baumannii in clinical settings. Previous studies showed that these transporters are tightly integrated into the physiology of A. baumannii and have diverse functions. However, for many of the efflux pumps, such functions remain poorly defined. In this study, we characterized two putative drug efflux pumps, AmfAB and AmfCD (Acinetobacter Major Facilitator), that are homologous to EmrAB-like transporters from Escherichia coli and other Gram-negative bacteria. These pumps comprise the Major Facilitator Superfamily (MFS) transporters AmfB and AmfD and the periplasmic membrane fusion proteins AmfA and AmfC, respectively. We inactivated and overproduced these pumps in the wild-type ATCC 17978 strain and its derivative strains lacking the major efflux pumps from the Resistance–Nodulation–Division (RND) superfamily and characterized antibiotic susceptibilities and growth of the strains under stresses typical during human infections. We found that neither AmfAB nor AmfCD contribute to the antibiotic non-susceptibility phenotypes of A. baumannii. The two pumps, however, are critical for the adaptation and growth of the bacterium under acidic stress, whereas AmfCD also contributes to growth under conditions of low iron, high temperature, and in the presence of bile salts. These functions are dependent on the presence of the RND pumps, the inactivation of which further diminishes A. baumannii survival and growth. Our results suggest that MFS transporters contribute to stress survival by affecting the permeability properties of the A. baumannii cell envelope.